Large Basilar Aneurysm with Posterior Inferior Cerebellar Artery Stroke and Consequential Fatal Subarachnoid Hemorrhage. (17th September 2012) - Patel, Rohit; Allen, Brandon; Desai, Bobby
Abstract : Basilar artery aneurysm presenting a stroke is rare, and we present a case of this along with a discussion of the management options available.